2019
DOI: 10.1002/lary.28103
|View full text |Cite
|
Sign up to set email alerts
|

Eustachian tube dysfunction in children with cleft palate: A tympanometric time‐to‐event analysis

Abstract: Objectives To characterize the duration of Eustachian tube dysfunction in children with cleft palate compared to those without cleft palate by performing time‐to‐event analysis on tympanometric data. To determine predictive characteristics of earlier achievement of normal tympanograms in children with cleft palate. Methods Longitudinal tympanometric data from a minimum of 10 years at a single center were reviewed for children with cleft palate born in the years 2003 through 2007. Children with cleft lip withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
(36 reference statements)
1
6
0
Order By: Relevance
“…Patients with CP (Funamura et al, 2019a) and SMCP (Kwinter et al, 2018) are at higher risk for Eustachian tube dysfunction (ETD) than the general population. A recent study indicated that, among patients with CP, history of revision palatoplasty or speech surgery was a risk factor for ETD (Funamura et al, 2019b). This is consistent with our anecdotal institutional experience.…”
Section: Introductionsupporting
confidence: 91%
“…Patients with CP (Funamura et al, 2019a) and SMCP (Kwinter et al, 2018) are at higher risk for Eustachian tube dysfunction (ETD) than the general population. A recent study indicated that, among patients with CP, history of revision palatoplasty or speech surgery was a risk factor for ETD (Funamura et al, 2019b). This is consistent with our anecdotal institutional experience.…”
Section: Introductionsupporting
confidence: 91%
“…With cleft palates, muscles of the soft palate are not united at the median raphe and middle ear ventilation is not guaranteed. 4 Inflammatory and non-inflammatory effusion can therefore develop in the tympanic cavity and lead to hearing impairment. 5,19 In this study, 78 patients with cleft palate were included.…”
Section: Discussionmentioning
confidence: 99%
“…2 Due to the incomplete fusion of these muscles in the median raphe, 3 the Eustachian tube does not open correctly in patients with cleft palate. 4 Subsequently, inflammatory and non-inflammatory effusion of the tympanic cavity can occur. 5 In fact, more than 80% of patients with cleft deformity show pathologies of the middle ear in the first 2 years of their lives.…”
Section: Introductionmentioning
confidence: 99%
“…The orofacial cleft with the prevalence of one in 700 births is considered the most common birth anomaly [1]. Likewise, persistent eustachian tube dysfunction is thought to be the primary factor responsible for the higher rates of more serious middle ear pathology observed in children with cleft palate, such as tympanic membrane perforation, middle ear atelectasis, cholesteatoma, and otitis media with effusion (OME) [2]. Moreover, OME entangles approximately 30 to 40 % of children at least once while rising to more than 90 % in children with CP [3,4].…”
Section: Introductionmentioning
confidence: 99%